Better Multimethod Design: The Promise of Integrative Multimethod Research. (2nd January 2016) - Seawright, Jason
Abstract : As this symposium suggests, we are in the middle of a boom time for multimethod research in the social sciences. Gary Goertz's essay shows how case studies can test claims about causal pathways; this suggestion should be seen as an element of a broader set of possibilities. "Integrative multimethod designs" provide a family of compelling strategies for linking qualitative and quantitative components of an overall design, while also enhancing the quality of causal inferences. Given that rigorous and credible causal inferences are essential to both scholars and policymakers, integrative multimethod research designs deserve our attention.